Bacteriological and Physicochemical Quality of Drinking Water in Adis Kidame Town, Northwest Ethiopia. (10th February 2021) - Sitotaw, Baye; Geremew, Mulu
Abstract : Drinking water pollution and the resulting waterborne diseases have been among the major public health burden in low-income countries such as Ethiopia. A high prevalence of waterborne diseases, up to 65%, has been reported in Adis Kidame Town (Ethiopia). Moreover, there have been poor waste disposal practices in this town. Thus, this study aimed to assess bacteriological and physicochemical drinking water quality in Adis Kidame Town to get insight into any potential health risks due to waterborne diseases. A total of 90 water samples were analyzed for enumeration of coliform bacteria and basic physicochemical parameters. In this study, total and faecal coliform counts (CFU/100 ml) ranged from 0 to 23 and 0 to 18, respectively. In all cases, 89 and 77% of the water samples in terms of total and faecal coliforms, respectively, did not comply with WHO guidelines. The highest level of coliforms was found in drinking water samples from households' containers and taps, where 100% and 90% of samples were tested positive for total and faecal coliforms, respectively. Among the physicochemical parameters recorded, only temperature and residual chlorine did not comply with WHO guidelines. Temperature values in all samples ranged from 20 to 28°C, while the values of residual chlorine were below the recommended range in the 56.7% of water samples from the reservoir and almost in all (96.7%) water samples from the taps and households' containers. High coliform count in the water system demands proper chlorination, regular inspection of the distribution line, and good hygienic practices to improve the microbiological quality of drinking water in Adis Kidame Town.